Security control of cyber–physical system based on switching approach for intermittent denial-of-service jamming attack. (September 2020) - Ge, Hui; Yue, Dong; Xie, Xiangpeng; Dou, Chunxia; Wang, Shuzheng
Abstract: In this study, the effects caused by intermittent denial-of-service jamming attack (I-DoS-JA) on different communication channels and communication topology transformations have been deeply analyzed. According to the analyzation, each different communication topology is taken as a subsystem of switching system. Based on switching system, finite-time nonlinear system robust stability conditions are derived. Both the theoretical deduction and example simulation have corroborated that this approach has special effective in resisting the intermittent DoS attack. Highlights: Unlike previous work, cyber-attack effects are considered from the viewpoint of transformations of the communication topology. I-DoS-JA will cause the changes of communication topology, and all of the changes of the communication topology are modeled as a switching system. In order to representative of CPS, nonlinear system is studied, and finite-time robust control conditions are derived, the actual meaning of this study is significant.